Evaluación operativa de una metodología no destructiva para la determinación del módulo de elasticidad dinámico del Pino híbrido F1. - Rotundo, Cristian Andres; Winck, Rosa Ángela; Gauchat, Maria Elena; Belaber, Ector (Facultad de Ciencias Forestales, Universidad Nacional de Misiones., 2022)
Evaluation of parameters that define quality in breeding programs is fundamental in the decision-making. The use of non-destructive methodologies simplifies this issue. The acoustic tools are based on the recording of wave stress, it is necessary to adjust the measurement technique looking for an acceptable cost/accuracy ratio. Correlations between them were found, so that three registrations of SWT would be sufficient for acceptable accuracy values.